2015
DOI: 10.1113/jp270238
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor blockade improves pulmonary gas exchange but decreases exercise performance in healthy humans

Abstract: Key pointsr At rest, dopamine induces recruitment of intrapulmonary arteriovenous anastomoses (IPAVA) and increases venous admixture (i.e.Q s /Q t ).r Dopamine increases during exercise, and may be partly responsible for exercise-induced IPAVA recruitment.r In this study, we antagonized dopamine receptors with metoclopramide, and observed improved pulmonary gas exchange but no difference in IPAVA recruitment during exercise.r Dopamine blockade decreased cardiac output at peak exercise, resulting in decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…These studies showed that dopamine receptor agonists improve exercise tolerance only under conditions of thermal stress (Roelands et al., ; Watson et al., ). Consistent with work in humans (Tedjasaputra et al., ) and animals (Balthazar, Leite, Ribeiro, Soares, & Coimbra, ), dopamine receptor blockade reduced exercise tolerance. In our previous work, the reduction in time‐to‐exhaustion with dopamine blockade was explained in part by a reduction in trueQ̇ and stroke volume (Tedjasaputra et al., ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…These studies showed that dopamine receptor agonists improve exercise tolerance only under conditions of thermal stress (Roelands et al., ; Watson et al., ). Consistent with work in humans (Tedjasaputra et al., ) and animals (Balthazar, Leite, Ribeiro, Soares, & Coimbra, ), dopamine receptor blockade reduced exercise tolerance. In our previous work, the reduction in time‐to‐exhaustion with dopamine blockade was explained in part by a reduction in trueQ̇ and stroke volume (Tedjasaputra et al., ).…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with work in humans (Tedjasaputra et al., ) and animals (Balthazar, Leite, Ribeiro, Soares, & Coimbra, ), dopamine receptor blockade reduced exercise tolerance. In our previous work, the reduction in time‐to‐exhaustion with dopamine blockade was explained in part by a reduction in trueQ̇ and stroke volume (Tedjasaputra et al., ). However, in the current study, we did not find any change in stroke volume or trueQ̇ with D 2 ‐receptor blockade.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition, the coefficient of variations for PnormalO2 (1.6%) and PnormalCO2 (2.2%) were small, and similar to values seen following immediate analysis using the same blood gas analyser (Tedjasaputra et al . ), suggesting no additional variance as would have been expected from inadvertent bubble contamination.…”
Section: Discussionmentioning
confidence: 90%